Evaluation of degradation of organophosphate insecticide residues in stored corn (Zea mays L.) grains - Strada, Julieta; Bruno, Cecilia; Nassetta, Mirtha M.; Balzarini, Mónica; Conles, Martha Y.; Rojas, Dante Emanuel; Ricca, Alejandra Patricia; Cristos, Diego Sebastian; Martinez, Maria Jose (Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2024)
The aims of this work were to monitor the dissipation dynamics of the organophosphate insecticides applied to corn grains stored in supervised experiments, establish the dissipation dynamics and determine the minimum period post application necessary to comply with the established commercial standards. The insecticides dichlorvos (DDVP), chlorpyrifosmethyl+deltamethrin (CPM) and pirimiphos-methyl (PMM) were applied to maize grains, which were then stored for 120 days. The samples were processed and extracted using the QuEChERS technique and the pesticide residues were identified and quantified by gas chromatography-mass spectrometry. Deltamethrin residues were not analized. After 90 days of storage, more than 80% of the initial residue had been degraded, and after 120 days the residues were below the detection limit (LoD). DDVP, CPM and PMM residues followed a first order degradation dynamics [Ct = C0×e(-kt)], with k values of 0.384, 0.025 and 0.020 and estimated half-lives of 1.8, 27.7 and 34.7 days, respectively. These results show that at recommended dosages, the insecticides CPM and PMM are safe for use on stored maize grains; DDVP results provide additional evidence further reasserting its prohibition, which dates back to 2018.